The effect of free writing technique on students’ writing ability - Asima Rohana Sinaga; Tiarma Intan Marpaung; Rudiarman Purba; Firinta Togatorop (STABN RADEN WIJAYA WONOGIRI, 2022)
The purpose of this research is to solve students' problems in writing narrative text, such as they lack vocabulary and they are difficult in certain generic structures. Students are not interested in Writing skills. Students still have difficulty expressing their ideas and they are bored in writing. Students' writing skills, especially narrative texts, are still low. This research is an experimental research. The purpose of this study was to find out which is more significant between the influence of Free Writing Techniques on Students' Writing Ability in writing narrative texts. Teaching writing narrative texts using free writing techniques or teaching writing narrative texts using conventional methods. The research design used in this study was a quasi-experimental research. The score data was taken from class XI students of SMA N. 5 Pematangsiantar. Which consists of 150 students who were selected by taking classes XI IA3 and XI IA4 as samples. In this study, the scores for writing narrative texts in the control group and the experimental group were used as data collection. There are two data used in this study. Namely: pre-test and post-test. The data were analyzed using the t-test formula. After analyzing the data, the results showed that the t-test was 2.72 and t-table = 2.003. The results showed that the t-test value was higher than the t-table t-test > t-table (2.72 > 2.003). It can be concluded that the application of Free Writing Techniques has a significant effect on Students' Ability in Writing Narrative Texts.